Efficient One-Pot Synthesis of Alkyl 3-[4-(Aryl or Heteroaryl)-1H-1,2,3-triazol-1-yl]thieno[3,2-b]pyridine-2-carboxylates by ‘Click’ Cu(I)-Catalyzed Azide–Alkyne Cycloaddition - Rodrigues, Juliana M.; Queiroz, Maria-João R. P. (Synthesis, 2016)
An efficient one-pot synthesis of several new alkyl 3-[4-(aryl or heteroaryl)-1H-1,2,3-triazol-1-yl]thieno[3,2-b]pyridine-2-carboxylates has been performed by in situ azidation of alkyl 3-aminothieno[3,2-b]pyridine-2-carboxylates followed by Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC). Both reactions were carried out at room temperature, the first using tert-butyl nitrite and TMSN3 in MeCN for 2 hours and the latter using several (hetero)arylalkynes, CuI, and Et3N in MeCN for very short reaction times (15–30 min). The active Cu(I) species was used directly, instead of the commonly employed Cu(II) species (CuSO4) with a reducing agent (sodium ascorbate) to generate Cu(I) in situ, which did not work in our case. This one-pot process showed wide scope and the products, which may have biological activity, were obtained in good to high yields with no need for chromatographic purification, thus fulfilling the criteria of ‘click’ chemistry. To our knowledge it is the first time that this methodology, using these conditions, has been applied to a heterocyclic moiety.
Keywords: thieno[3,2-b]pyridines; azides; CuAAC; click chemistry; 1,2,3-triazoles